EXPLORING MORALITY AMONG ORPHANS: A STUDY OF AKHLAQ AND SOCIAL STANDARDS IN PUSAT JAGAAN HEMBUSAN KASIH SAYANG - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Muhammad Syaheed Mohamad Asri; Faizah Muhamad; Farzana Tarmizi; Nur Najwa Mohd Idris (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores the Islamic perspective on the care and treatment of orphans, focusing on their moral development within an institutional setting. Islamic teachings emphasize the holistic welfare of orphans, advocating for their physical, emotional, and spiritual well-being. This notion is grounded in the Quran and Hadith, where caring for orphans is not only a moral obligation but a means to attain spiritual reward. The study employs a qualitative cross-sectional design, using self-report questionnaires distributed among 50 children at Pusat Jagaan Hembusan Kasih Sayang, Kuantan. The questionnaire assesses various aspects of morality (’akhlaq’) in relation to God, guardians, peers, and daily life. Results show a strong adherence to Islamic practices among the children, such as prayer, Quran recitation, and fasting, reflecting their spiritual upbringing. Their interactions with guardians and peers demonstrate respect, assistance, and effective conflict resolution, aligning with Islamic values of empathy and social harmony. Daily habits like tidiness and honesty are indicative of the institution’s success in instilling Islamic principles of cleanliness and integrity. The study highlights the significant role of institutions like Pusat Jagaan Hembusan Kasih Sayang in shaping the moral development of orphans. These institutions provide not only physical care but also moral and spiritual guidance, crucial for children lacking familial support. The findings suggest that integrating religious teachings into the upbringing of children fosters a strong moral compass, preparing them to be responsible and ethical members of society. Overall, this research underscores the potential of religious education in promoting moral and ethical values in young individuals and calls for its replication in other childcare and educational settings. Future research could explore the long-term societal impact of such upbringing and the challenges faced by caregivers and educators in reinforcing these values.